Distribution of mercury species in different tissues and trophic levels of commonly consumed fish species from the south Bay of Biscay (France). (May 2021) - Mille, Tiphaine; Bisch, Amaëlle; Caill-Milly, Nathalie; Cresson, Pierre; Deborde, Jonathan; Gueux, Aurore; Morandeau, Gilles; Monperrus, Mathilde
Abstract: Mercury (Hg) is a contaminant of global concern in marine ecosystems, notably due to its ability to accumulate and concentrate in food webs. Concentrations of total mercury (THg), methylmercury (MeHg) and inorganic mercury (IHg) were assessed and compared in different tissues (liver, muscle, and gonads) of three common fish species (hake Merluccius merluccius, red mullet Mullus surmuletus, and sole Solea solea ) from the continental shelf from the southern part of the Bay of Biscay. Several studies investigated Hg concentration in fish muscle, but few assessed concentrations in other organs, despite the importance of such data to understand contaminant organotropism and metabolization. Results showed that trophic position and feeding habitat are required to understand the variability of Hg concentration in muscle between fish species. In addition, high MeHg/THg ratio in muscle could be explained by the predatory behavior of the studied fish species and the biomagnification of this Hg species within the food web, MeHg. Despite differences between species, Hg concentration was always higher in muscle (from 118 ± 64 to 338 ± 101 ng g −1 w.w.) and liver (from 122 ± 108 to 271 ± 95 ng g −1 w.w.). These results can be related to physiological processes especially the MeHg detoxification strategies. Highlights: High MeHg/THg ratio in fish muscle explained by MeHg biomagnification. Trophic position and feeding habitat cause Hg variation in fish muscle. Hg concentration was higher in muscle and liver for all fish species. Difference in Hg distribution could be related to differential MeHg detoxification strategies.